English speech rhythm in instructed learners. Its development as shown by VarcoV - Espinosa, Gonzalo Eduardo (2019)
Speech rhythm is viewed as the product of different phonetic and phonological properties. This work shows the rhythmic acquisition of instructed learners of English as an L2 whose mother tongue is Spanish. Two main variables are considered: levels of language proficiency at university and type of elicitation task. Taking into account that rhythm can be measured acoustically, the production of speech is computed by means of the metric VarcoV, which considers the duration of vocalic intervals. The metric measurements reflect the development of L2 speakers‟ speech in direction to a more native-like rhythm affected by the type of task.